Fleshy fungi of Garhwal Himalaya: The genus Russula - and R.D. GAUR, R.P. BHATT, V.K. BHATT (Indian Phytopathology, 2002)
Four taxa of the genus Russula Pers. ex S. F. Gray, R. albida Peck, R. amoenolens Romagn., R.brevipes Peck var. acrior Shaffer and R. dissimulans Shaffer collected from Garhwal Himalaya are illustrated and described for the first time from India.